2015 IEEE International Symposium on Power Line Communications and Its Applications (ISPLC) 2015
DOI: 10.1109/isplc.2015.7147582
|View full text |Cite
|
Sign up to set email alerts
|

Constant envelope OFDM transmission over impulsive noise power-line communication channels

Abstract: Signal blanking is a simple and efficient method to reduce the effect of impulsive noise over power-line channels. The efficiency of this method, however, is found to be not only impacted by the threshold selection but also by the average peak-to-average ratio (PAPR) value of the orthogonal frequency division multiplexing (OFDM) signals. As such, the blanking capability can be further enhanced by reducing the PAPR value. With this in mind, in this paper we evaluate the performance of constant envelope OFDM (CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…In this paper, we use the SLM technique, which already improves the blanking performance [29], and analyse its effect on the optimized threshold. The results of the study are in agreement with the conclusions presented in [29] and [37]. With the increase of phase vectors, the optimized threshold value remains constant regardless of the received signal characteristics.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this paper, we use the SLM technique, which already improves the blanking performance [29], and analyse its effect on the optimized threshold. The results of the study are in agreement with the conclusions presented in [29] and [37]. With the increase of phase vectors, the optimized threshold value remains constant regardless of the received signal characteristics.…”
Section: Introductionsupporting
confidence: 90%
“…This optimized threshold results in increased output Signal-to-Noise Ratio (SNR) for different IN probabilities, as compared to fixed threshold. It has already been shown that an optimized threshold can become independent of IN probability and initial estimation through PAPR reduction [29] and phase modulator transform system, referred as Constant Envelope OFDM (CE-OFDM) [37]. In this paper, we use the SLM technique, which already improves the blanking performance [29], and analyse its effect on the optimized threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it worthy to mention that [2] has studied the use of MC transform in mitigating IN, however the study was not compared to any other known companding transform. Other PAPR reduction schemes used are partial transmit sequence and constant envelope OFDM [14,15] which do not consider companding or ICF techniques. process.…”
Section: Papr Reduction Schemesmentioning
confidence: 99%
“…In other words, reducing the peak-to-average power (PAPR) Being complex, we can separate the output time domain signal into parts such as x i (n) and x r (n) which are from x (n) = x r + jx i , In the literature, OFDM system dispensing with constant enve-∀n = 0, 1, · · · , N − 1 where j − = √ 1. We can also estimate the lope has been proposed to reduce the PAPR of PLC-OFDM systems and thus enhance the mitigation of IN [15] through the memoryless nonlinearity pre-processing [22]. Also, using partial transmit sequence (PTS) the OFDM signal transmission over powerline channel can enhance the reduction of IN effects [14].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of improving IN mitigation by reducing PAPR at transmitter was first introduced in [9]. In addition, OFDM systems dispensing with a flat envelope was later proposed to reduce PAPR and avail amplitude distributions that can help mitigate IN [10], however the scheme imposes computational burden on the system. While the clipping or companding PAPR techniques are performed after OFDM modulation at the transmitter [6], [7], the nonlinear blanking or clipping to mitigate IN are performed at the receiver [11] before OFDM demodulation.…”
Section: Introductionmentioning
confidence: 99%